1999
DOI: 10.1161/01.cir.99.7.861
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Receptor Antagonist Gene Polymorphism and Coronary Artery Disease

Abstract: IL-1RN*2 was significantly associated with SVD. A difference in genetic association between SVD and MVD was also apparent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
152
4
6

Year Published

2001
2001
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(170 citation statements)
references
References 33 publications
8
152
4
6
Order By: Relevance
“…In our hands, the frequency of the TNF-a -308A allele in the control group was similar to that observed in CAD patients. The lack of association between -308 TNF-a polymorphism and CAD is consistent with other studies (24,28), and confirm the results of Francis et al (29) who found no association between TNF-a -308A allele and clinically or angiographically-documented coronary stenosis. Our data confirm some previous studies that investigated Caucasian populations and failed to demonstrate that this locus could be a marker for greater risk of CAD.…”
Section: Discussionsupporting
confidence: 91%
“…In our hands, the frequency of the TNF-a -308A allele in the control group was similar to that observed in CAD patients. The lack of association between -308 TNF-a polymorphism and CAD is consistent with other studies (24,28), and confirm the results of Francis et al (29) who found no association between TNF-a -308A allele and clinically or angiographically-documented coronary stenosis. Our data confirm some previous studies that investigated Caucasian populations and failed to demonstrate that this locus could be a marker for greater risk of CAD.…”
Section: Discussionsupporting
confidence: 91%
“…Previously defined examples include polymorphisms in TNF␣ and IL-1ra that have been shown to have certain prognostic significance in malaria and ischaemic heart disease respectively. 24,25 Similarly, a number of polymorphisms in TNF␣ and IL-1␤ have been reported to be associated with rheumatoid arthritis severity. [26][27][28] The novel Mif gene polymorphism that we have identified is associated with reduced MIF promoter activity, and the presence of this genotype in the homozygous state appears to be associated with a reduced risk of severe rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IL-1ra levels are increased in patients with angina, and specific polymorphisms in the IL-1ra gene are associated with coronary artery disease. 13,14 Studies with IL-1 antagonists would be required to test the causality of these associations. This study does not rule out contribution by other important proinflammatory and anti-inflammatory cytokines, and it is possible that the IL-1ra simply acts as a surrogate marker for some other cytokine or mediator that causes endothelial dysfunction.…”
Section: Aspirin Pretreatment Preserves Endothelial Functionmentioning
confidence: 99%